Importance of cardiac imaging assessment of epicardial adipose tissue after a first episode of myocardial infarction - Islas, Fabián; Gutiérrez, Eva; Cachofeiro, Victoria; Martínez-Martínez, Ernesto; Marín, Gema; Olmos, Carmen; Carrión, Irene; Gil, Sandra; Mahía, Patricia; Cobos, Miguel Ángel; de Agustín, Alberto; Luaces, María (Frontiers in Cardiovascular Medicine, 2022)
Background Over the past years, information about the crosstalk between the epicardial adipose tissue (EAT) and the cardiovascular system has emerged. Notably, in the context of acute myocardial infarction (AMI), EAT might have a potential role in the pathophysiology of ventricular structural changes and function, and the clinical evolution of patients. This study aims to assess the impact of EAT on morpho-functional changes in the left ventricle (LV) and the outcome of patients after an AMI. Methods We studied prospectively admitted patients to our hospital with a first episode of AMI. All patients underwent percutaneous coronary intervention (PCI) during admission. Transthoracic echocardiography (TTE) was performed within 24–48 h after PCI, as well as blood samples to assess levels of galectin-3 (Gal-3). Cardiac magnetic resonance (CMR) was performed 5–7 days after PCI. Clinical follow-up was performed at 1 and 5 years after MI. Results Mean age of our cohort (n = 41) was 57.5 ± 10 years, and 38 (93%) were male. Nine patients had normal BMI, 15 had overweight (BMI 25–30), and 17 were obese (BMI > 30). Twenty three patients (56%) had ≥ 4 mm thickness of EAT measured with echo. In these patients, baseline left ventricular ejection fraction (LVEF) after AMI was significantly lower, as well as global longitudinal strain. EAT thickness ≥ 4 m patients presented larger infarct size, higher extracellular volume, and higher T1 times than patients with EAT < 4 mm. As for Gal-3, the median was 16.5 ng/mL [12.7–25.2]. At five-year follow-up 5 patients had major cardiac events, and all of them had EAT ≥ 4 mm. Conclusions Patients with EAT >4 mm have worse LVEF and GLS, larger infarct size and longer T1 values after a MI, and higher levels of Gal-3. EAT >4 mm was an independent predictor of MACE at 5-year follow-up. EAT thickness is a feasible, noninvasive, low-cost parameter that might provide important information regarding the chronic inflammatory process in the myocardium after an infarction.